2022
DOI: 10.3390/ijms231810363
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function Dynamin-2 Mutations Linked to Centronuclear Myopathy Impair Ca2+-Induced Exocytosis in Human Myoblasts

Abstract: Gain-of-function mutations of dynamin-2, a mechano-GTPase that remodels membrane and actin filaments, cause centronuclear myopathy (CNM), a congenital disease that mainly affects skeletal muscle tissue. Among these mutations, the variants p.A618T and p.S619L lead to a gain of function and cause a severe neonatal phenotype. By using total internal reflection fluorescence microscopy (TIRFM) in immortalized human myoblasts expressing the pH-sensitive fluorescent protein (pHluorin) fused to the insulin-responsive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(106 reference statements)
1
3
0
Order By: Relevance
“…Particularly, we showed recently that the dynamin-dependent endocytosis induced after short depolarizations, like the one shown in the first section of this paper, is also dependent on polymerized F-actin (Montenegro et al 2021). In the present work, we observed that p.A618T and p.S619L mutations disrupt the formation of actin filaments in chromaffin cells, and very recently we described a similar effect of both mutations in immortalized human myoblasts (Bayonés et al, 2022a). It is important to note that, from the beginning, dynamin was associated with actin dynamics (Gu et al, 2010;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Particularly, we showed recently that the dynamin-dependent endocytosis induced after short depolarizations, like the one shown in the first section of this paper, is also dependent on polymerized F-actin (Montenegro et al 2021). In the present work, we observed that p.A618T and p.S619L mutations disrupt the formation of actin filaments in chromaffin cells, and very recently we described a similar effect of both mutations in immortalized human myoblasts (Bayonés et al, 2022a). It is important to note that, from the beginning, dynamin was associated with actin dynamics (Gu et al, 2010;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…Dynamin-2 was classically associated to endocytosis, however it has also been implicated in other cellular processes, like vesicle trafficking, exocytosis, and regulation of actin filament dynamics (González-Jamett et al, 2013b). Recently, by using total internal reflection fluorescence microscopy in immortalized human myoblasts, we reported that p.A618T and p.S619L dynamin-2 mutations impairs Ca 2+ -induced exocytosis of GLUT4 containing vesicles (Bayonés et al, 2022a). These two mutations have been linked to severe neonatal forms of CNM (Böhm et al, 2012), a form of skeletal muscle hereditary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle atrophy also represents one of the most important symptoms of congenital genetic muscle disorders, such as centronuclear myopathy, caused by mutations in the genes encoding proteins involved in membrane trafficking and remodeling. In an interesting study by Bayones et al [ 13 ], the authors explore the mutations of dynamin-2 (namely, p.A618T and p.S619L), a mechano-GTPase that remodels membrane and actin filaments, and their influence on myoblast exocytosis. The results of the study indicate that both mutations impair the exocytosis by affecting the fusion pore dynamics and disrupting the formation of actin filaments, which may disturb the plasmalemma expression of functional proteins such as the glucose transporter GLUT4 in skeletal muscle cells, impacting the physiology of the skeletal muscle tissue.…”
mentioning
confidence: 99%